Effect of restricting the legal supply of prescription opioids on buying through online illicit marketplaces: interrupted time series analysis. (13th June 2018) - Martin, James; Cunliffe, Jack; Décary-Hétu, David; Aldridge, Judith
Abstract: Objective: To examine the effect on the trade in opioids through online illicit markets ("cryptomarkets") of the US Drug Enforcement Administration's ruling in 2014 to reschedule hydrocodone combination products. Design: Interrupted time series analysis. Setting: 31 of the world's largest cryptomarkets operating from October 2013 to July 2016. Main outcome measures: The proportion of total transactions, advertised and active listings for prescription opioids, prescription sedatives, prescription steroids, prescription stimulants, and illicit opioids, and the composition of the prescription opioid market between the US and elsewhere. Results: The sale of prescription opioids through US cryptomarkets increased after the schedule change, with no statistically significant changes in sales of prescription sedatives, prescription steroids, prescription stimulants, or illicit opioids. In July 2016 sales of opioids through US cryptomarkets represented 13.7% of all drug sales (95% confidence interval 11.5% to 16.0%) compared with a modelled estimate of 6.7% of all sales (3.7% to 9.6%) had the new schedule not been introduced. This corresponds to a 4 percentage point yearly increase in the amount of trade that prescription opioids represent in the US market, set against no corresponding changes for comparable products or for prescription opioids sold outside the US. This change was first observed for sales, and later observed for product availability. There was also a change in the composition of the prescription opioid market: fentanyl was the least purchased product during July to September 2014, then the second most frequently purchased by July 2016. Conclusions: The scheduling change in hydrocodone combination products coincided with a statistically significant, sustained increase in illicit trading of opioids through online US cryptomarkets. These changes were not observed for other drug groups or in other countries. A subsequent move was observed towards the purchase of more potent forms of prescription opioids, particularly oxycodone and fentanyl.